Horizontal FDI in a dynamic Cournot-Oligopoly with endogenous entry - Laszlo Goerke (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2020)
Entry in a homogeneous Cournot-oligopoly is excessive if and only if there is business-stealing (Amir et al. 2014). The excessive entry prediction has been derived primarily for closed economies and using a welfarist benchmark. We extend this framework and allow for (1) horizontal FDI in a multi-period setting and (2) interest group-based government behaviour. Opening the market to greenfield investments from abroad tends to aggravate the entry distortion. Moreover, market opening may reduce welfare if a more pronounced entry distortion dominates the gain in consumer surplus. Finally, a government, which places sufficiently little weight on the interests of consumers, will object to market opening, even if welfare rises.
Keywords: D43; D72; F21; L13; 330; Excessive Entry; Cournot-Oligopoly; Horizontal FDI; Political Support Function